The practice of adapting a post-industrial facility into a museum of technology - Mierosławski, Paweł (Z praktyki adaptacji obiektu poprzemysłowego na muzeum techniki, 2023)
The subject of the article is the adaptation of the historic Steam Locomotive Works in Skierniewice for the purposes of a “living” technical museum. The author, using his own thirty years of experience, presented the problem of reconciling the possibility of showing the old technologies of railroad work with the introduction of new functions to historic buildings. The article describes reaching a compromise between the need to preserve historic equipment and infrastructure, as well as the visual qualities of individual objects, with the requirements of current regulations and the desire to show the gathered collection in a way that is interesting and safe for visitors. The example presented in the paper concerns the territorially and cubically largest complex of historic railroad buildings in Poland, where the scale of adaptation works is the largest. The complex is also the oldest surviving relic of the technical facilities of the first Polish railroad line – the Warsaw–Vienna Iron Road. It was built in 1845 and went through several phases of expansion. At present, it preserves buildings from 1859–1943 and technical structures related to the operation of steam locomotives. In 1992, with the end of operation by the railway, the complex was loaned, and in 2002 it was transferred to a non-governmental organization for museum purposes. It is listed in the register of historical monuments under No. 964A. The Skierniewice Locomotive Deport is an example of the success of many years of renovation and adaptation work conducted by an investor that is a non-governmental organization with a modest budget and bases its activities solely on the unpaid work of volunteers.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2023, nr 3 (75), s. 61-72
Keywords: architektura; historic preservation; railroad monuments; living museum; ochrona zabytków; zabytki kolejnictwa; żywe muzeum